Sistem Informasi Persediaan Barang Menggunakan Framework Bootstrap dan Bahasa Pemrograman PHP MYSQL - Nurjani, Muhamad Ari; Mulyadi, Iman; Taryanto, Ardi (Computer Based Information System Journal, 2021)
Online shop companies that are currently running only use Microsoft excel in recording, selling, purchasing for inventory. In making invoices and purchases still use only notes. With this system running, there are many errors that often occur, such as the loss of sales invoices, the loss of travel documents and which result in no evidence of transactions that have occurred. Therefore we need a computerized system that can help to make sales purchases more easily and can check stock items very easily and accurately. The design of this system starts from the warehouse first to record incoming goods then make a purchase invoice and here the warehouse confirms to the shop owner, if approved, the owner will ask the admin to make stock adjustments, after the stock is reduced, the admin will confirm to the Warehouse and the Warehouse will make a travel document to be continued to the consumer.